ANALISIS PENGUKURAN KINERJA KEUANGAN PADA PEMERINTAH KOTA TOMOHON - Sumual, Christian D.; Kalangi, Lintje; Gerungai, Natalia Y. T. (Universitas Sam Ratulangi, 2017)
Information generated from financial statements will be useful if the information is understood and used by users in analyzing a report and management of local finances. For that we need to measure the financial performance of the government, how far the progress achieved by the government of Tomohon. The research was conducted in the financial management, revenue and assets of Tomohon. The data used is quantitative in the form of Budget Realization Report (LRA), the method used is quantitative to measure financial performance with Financial ratios. The results show that the financial performance of Tomohon is not good, where the financial performance in 2013-2016, for the effectiveness ratio is above 90% -100%. While the efficiency ratio and the independence ratio per year are not running well. Keywords: Influence ofÂ financial performance measurement